Born to love you - Martin, Coco; Quinto, Angeline; Tantay, Al; De Guzman, Malou; Robocan, Jerome Chavez; Santos-Consio, Charo; Santos, Malou; Nacianceno, Rodel P. (Quezon City Star Cinema Producrtions, 2012)
Coco and Angeline play Rex and Joey respectively. Rex is a photographer who struggled his way just to survive. He comes from a broken family and practically grew up his lonesome. Joey is a tourist guide in search for her true father. She comes from a poor family who also struggles with the day to day realities of life. "born to love you" is more than just a love story of the two lead characters who affect each other's lives as they fell in love but it also celebrates the beauty of life, love, relationships and existence.
VCD
Executive producers, Charo Santos-Concio, Malou Santos, Rodel P. Nacianceno ; screenplay, Rodel P. Lindayag ; director, Jerome Chavez Pobocan.
Coco Martin, Angeline Quinto, Al Tantay, Malou De Guzman, Jojit Lorenzo, Eda Nolan.
Keywords: Born to love you (Motion picture).; Romance films; Feature films